AI in Logistics: Smarter Inventory and Shipment Optimization - Samuel Tatipamula (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Artificial intelligence is revolutionizing logistics operations, transforming traditional supply chain processes into dynamic, data-driven systems that continuously adapt to changing conditions. This technical article explores how AI technologies are addressing critical inefficiencies in inventory management and shipment optimization that have historically plagued logistics operations. Advanced machine learning algorithms now enable unprecedented demand forecasting accuracy, dynamic inventory optimization, and intelligent route planning that considers multiple constraints simultaneously. These systems process real-time data from diverse sources to generate actionable insights that balance competing priorities such as cost reduction, service level improvements, and sustainability goals. The implementation of AI-powered solutions, while facing challenges including data quality issues and organizational resistance, offers substantial competitive advantages through reduced operational costs, improved delivery precision, and enhanced customer satisfaction. As technologies including digital twins, autonomous vehicles, blockchain, and quantum computing continue evolving, they promise to further transform logistics operations into increasingly automated and resilient systems capable of self-optimization.